Efektivitas Penggunaan Quick Response Code Indonesian Standard (QRIS) Untuk Meningkatkan Omzet Penjualan pada UMKM Kuliner di Kota Makassar - Risal, Risal; Yusriadi Hala; Rostiaty Yunus; Tamsil, Tamsil (Al-Buhuts, 2024)
The Effectiveness of Using the Indonesian Standard Quic Response Code (QRIS) to Increase Sales Turnover in Culinary MSMEs in Makassar City. The aim of this research is to find out the obstacles and obstacles that can occur in implementing the Indonesian Standard Quick Response Code (QRIS) payment. This research method uses a qualitative approach, while this type of research is descriptive research. The location of the research was in Makassar City, District. Panakukkang and District. Tamalate. Data collection techniques use observation, interviews and documentation. Data analysis tecniques use data reduction, data presentation, and verification or efforts to draw conclusion. The validity of the data uses source triangulation, engineering triangulation and time triangulation techniques. Based on the research results, it can be concluded. Effectiveness of using QRIS in current MSME food and beverage sales transactions in Makassar City. It can be said to be effective in all effectiveness benchmarks that the aouther uses, including: (a). System quality, (b). Information quality, (c). Quality of service, (d). User, (e). User satisfaction and, (f). Net profit. Barriers or obstacles are disruptions to the network.